HASIL TANAMAN PADI (Oryza sativa L Var. Inpari) AKIBAT PUPUK BIOSLURRY DAN PEMBENAH TANAH PADA TIGA JENIS TANAH - apitya muktifani; Sumarsono Sumarsono; Didik Wisnu Widjajanto (Jurnal Agroekoteknologi, 2022)
ABSTRACTThe impact of soil fertility degradation is the continuous use of inorganic fertilizers, which caused soil organic matter and rice production degradation. The study was conducted to obtain the optimal dose of bioslurry fertilizer for rice growth and production in andosol, regosol, and aluvial soil types without or with soil amendment. The  experiment used split split plot with Completely Randomized Design and three replication. The main plot is soil type, L1:Andosol, L2:mediterranean, and L3:aluvial. The subplots is soil amendment, R1:without amendment, and R2:with amendment. The sub subplots used is bioslurry fertilizer, P1:125kgN/ha, P2:1,5 x 125kgN/ha, and P3: 2 x 125kgN/ha. The results showed that interaction of soil amendment and bioslurry dose had a significant (P<0.05) on the growth and production of Inpari rice. The interaction of soil type and amendment showed significance (P<0.05) in plant height, number of tillers, parameters with highest result at aluvial soil with amendment. The interaction of amendment and bioslurry showed significance (P<0.05) on fresh weight and dry weight of grain parameter with highest result at dose of 2 x 125kgN/ha with amendment. The interaction between soil type, amendment, and bioslurry show significance (P<0.05) at weight of 1000 seeds, and production with ameliorant parameters with highest result in aluvial soil types with 2 x 125kgN/ha dose. Alluvial soil with amendment and bioslurry 2 x 125 kg N/ha dose gave the highest rice production yield of 15,94 t/ha. Keywords: amendment, bioslurry, rice, soil type